The complete mitochondrial genome of the Basidiomycete fungus Pleurotus cornucopiae (Paulet) Rolland. Issue 1 (2nd January 2018) - Xu, Li-Ming; Hinsinger, Damien Daniel; Jiang, Guo-Feng
Abstract: Pleurotus cornucopiae is a commercial edible and medicinal fungus. Herein, we determined and analyzed its complete mitochondrial genome. The mitogenome length was 72, 134 bp with a GC content of 26.7%, contained 14 conserved protein coding genes, two rRNA genes ( rnl and rns ), ribosomal protein gene rps3 and 24 tRNA genes. Pleurotus cornucopiae has a similar gene content and gene order of the mitogenome as P. ostreatus and P. eryngii . A phylogenetic analysis based on complete mitogenome in related fungi showed that P. cornucopiae is a member of the order Agaricales, forming a clade with P. ostreatus and P. eryngii, with P. ostreatus as a sister taxa. The mitochondrial genome sequence of P. cornucopiae appeared a promising tool for further studies of the taxonomy and evolution of Pleurotaceae and Agaricales.